Imagining Polynesia: Heritage, Identity Politics and the Evolution of a New Rapa Nui architecture. (16th September 2021) - Hamilton, Sue; Huke, Hetereki; Seager Thomas, Mike
Abstract : Rapa Nui's prehistoric Polynesian heritage is iconic. From the later twentieth century the island's economy has been dependent on the tourism its prehistory attracts. However, until recently there has been little link between the modern built environment of Rapa Nui and its prehistoric past. This article tracks how during the late nineteenth and twentieth centuries, the island's traditional domestic architecture was supplanted first by colonial then early modern Chilean architecture. The remains of this transformation are fast disappearing through contemporary demolition and an associated rejection of the past that the introduced architecture represents. We highlight how contemporary Rapa Nui architecture instead actively references its iconic prehistoric Polynesian past and positions Rapa Nui in a Polynesian context, for the first time detailing this trajectory and identifying how elements of past artistic and architectural traditions have become incorporated into the architecture of the present. Instead of presenting the intervening period as one of loss of traditional identity, this in fact emphasises a subtle continuity of Rapanui (indigenous Rapa Nui islander) identity. The study is relevant to exploring how the interacting demands and expectations of identity politics and heritage tourism (here in a Polynesian context) can impact on contemporary local architecture and the visitor milieu, reflecting modern concepts which promote the preservation of some architectures and cultural attributes over others.